Decoding eumelanin's spin label signature: a comprehensive EPR analysis - Paulin, João Vitor; Graeff, Carlos Frederico de Oliveira [UNESP]; Mostert, A. Bernardus (Royal Society of Chemistry, 2024)
Eumelanin is a black-brown natural pigment found throughout nature. As a material class, it possesses unique physical and chemical properties that entice much attention from chemists, physicists, and material scientists due to its potential use in medical and sustainable organic (bio)electronics settings. To harness its potential, accurate spectroscopical characterization is a primary requirement for the efficient engineering of eumelanin-based electronic devices. A key spectroscopic technique is electron paramagnetic resonance (EPR) since the persistent paramagnetism of eumelanin is a spin-label signature of its molecular state. This review provides a comprehensive discussion on the origin of eumelanin paramagnetism through a multifrequency EPR approach and highlights the current multi-species point-of-view.
A decodificação da assinatura de spin da eumelanina: uma análise abrangente de EPR
Keywords: Melanin; Eeumelanin; Poly-indolequinone; Redox chemistry; Electron paramagnetic resonance